Preventive Behaviors Among Leukemia and Lymphoma Cancer Survivors: Results From the 2020 Behavioral Risk Factor Surveillance System Survey - Steven S. Coughlin, PhD, MPH; Biplab Datta, PhD; Ban Majeed, PhD (Elsevier, 2023)
Introduction: Maintaining a healthy lifestyle is an important factor in promoting positive outcomes for cancer survivors. Health behaviors, such as engaging in physical activity, not consuming large amounts of alcohol, abstaining from cigarette smoking, receiving routine immunizations, and undergoing recommended cancer screening tests, may lead to improved physical health, health status, and quality of life. Methods: We examined preventive behaviors among hematologic cancer survivors in a cross-sectional analysis, using data from the 2020 Behavioral Risk Factor Surveillance System. Results: Adherence to cancer screening test and immunization recommendations among hematologic cancer survivors compares favorably with that among persons with no history of cancer. However, no statistically significant differences in the frequency of current smoking, heavy drinking, and physical activity were observed across these 2 groups. No important differences were observed in health behaviors between male and female cancer survivors, except that female hematologic cancer survivors were more likely to adhere to influenza and pneumococcal pneumonia immunization recommendations than female survivors of other types of cancer, whereas no such differences were found among their male counterparts. Conclusions: Although hematologic cancer survivors were more adherent to preventive health behaviors such as cancer screening and immunization, they were not different from persons without any history of cancer in exhibiting behavioral risk factors such as smoking and heavy drinking. Intervention studies are needed to identify effective ways to assist hematologic cancer survivors to quit smoking and refrain from hazardous alcohol consumption.